(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Integration of clinical decision support systems (CDSS) into clinical practice commonly allows improvements in efficacy of diagnosis, treatment and observation of patients, particularly those with eye disease. Purpose: To substantiate and develop an automated CDSS for extraocular muscle pathology in strabismus. Material and Methods: We used polarized light to assess the parameters of interference patterns for 147 patients with strabismus due to abnormal structure and function of extraocular muscles. Results: The following informative interference pattern parameters were determined based on the results of studies and modeling of interference patterns: interference diamond diagonal segments, angles between two diagonal segments, and angles between the diagonal segment and relevant meridians. The main features of interference patterns for various types of strabismus were identified. An automated system using the above informative interference pattern parameters for clinical decision support for extraocular rectus muscle pathology in strabismus was proposed. Conclusion: Application of the proposed CDSS with enable the ophthalmologist to obtain information on the structural and functional state of the extraocular rectus muscles in 2 to 3 minutes. In addition, it will enable him/her to judge the state of the extraocular oblique muscles indirectly if the symmetrical corneal interference pattern is obtained for the strabismic eye.